Post-Fire Ship Hull Repair Method Considering Corrosion Rate and Mechanical Properties - Baihaqi, Imam; Supomo, Heri (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Ship accidents due to fire will result in several consequences, especially concerning the structure of the ship. The very high temperature of the ship fire will greatly affect the mechanical properties and corrosion resistance of the ship's construction materials after the fire. This study will investigate the relationship between mechanical properties and corrosion resistance of materials to the temperature that occurs during the fire. The mechanical properties are examined by testing the tensile strength of the material after the fire. As for corrosion resistance, corrosion speed testing will be carried out using the 3-electrode cell method. The experimental temperature variations used are 300°C, 500°C, 600°C, 700°C, and 900°C. Based on the results of the study, it can be concluded that the higher the fire temperature, the mechanical properties also increase. This increase in tensile strength reaches a culmination point at a temperature of 600°C and then tends to decrease with increasing fire temperature. As for the corrosion speed, the change phenomenon is also almost the same pattern. The higher the temperature of the ship fire, the corrosion speed will increase significantly. The increase in the corrosion rate value in post-burn ship materials will continue to increase. So based on the experiment, it can be concluded that post-burning material can still be refurbished if the temperature is <600°C, with a tensile strength of 445 MPa and a corrosion rate of 0.5 mmpy.